2010
DOI: 10.1186/1471-2164-11-660
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome profiling analyses during the lag phase uncover YAP1, PDR1, PDR3, RPN4, and HSF1 as key regulatory genes in genomic adaptation to the lignocellulose derived inhibitor HMF for Saccharomyces cerevisiae

Abstract: BackgroundThe yeast Saccharomyces cerevisiae is able to adapt and in situ detoxify lignocellulose derived inhibitors such as furfural and HMF. The length of lag phase for cell growth in response to the inhibitor challenge has been used to measure tolerance of strain performance. Mechanisms of yeast tolerance at the genome level remain unknown. Using systems biology approach, this study investigated comparative transcriptome profiling, metabolic profiling, cell growth response, and gene regulatory interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
148
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(156 citation statements)
references
References 88 publications
(119 reference statements)
8
148
0
Order By: Relevance
“…However, induction of stress-responsive genes was commonly observed when cells were treated with either furfural or HMF. Especially, Yap1, a major oxidative stress regulator, was identified as one of the key regulators involved in genomic adaptation to HMF in S. cerevisiae, suggesting that HMF might elicit oxidative stress (17,18). In agreement with the role for Yap1 in adaptation to HMF, the overexpression of YAP1 has been shown to increase tolerance to HMF and dilute acid spruce hydrolysates (18).…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…However, induction of stress-responsive genes was commonly observed when cells were treated with either furfural or HMF. Especially, Yap1, a major oxidative stress regulator, was identified as one of the key regulators involved in genomic adaptation to HMF in S. cerevisiae, suggesting that HMF might elicit oxidative stress (17,18). In agreement with the role for Yap1 in adaptation to HMF, the overexpression of YAP1 has been shown to increase tolerance to HMF and dilute acid spruce hydrolysates (18).…”
mentioning
confidence: 68%
“…Previous DNA microarray experiments have revealed that Yap1 is one of the key regulators involved in genomic adaptation to HMF in S. cerevisiae (17). Yap1 is activated by H 2 O 2 and thiolreactive electrophiles through different mechanisms (27).…”
Section: Furfural and Hmf Induce Intracellular Ros Accumulation In Smentioning
confidence: 99%
See 2 more Smart Citations
“…Several genes encoding oxidoreductases that reduce furfural and 5-hydroxymethylfurfural (5-HMF) (a dehydration product of hexose sugars) have been implicated in furan tolerance in Saccharomyces cerevisiae (2,20,21,22,23) and in Escherichia coli (29)(30)(31)38). Gene array studies identified more than 365 genes that changed in expression level during an HMF challenge, and these changes are proposed to be mediated by at least 5 different regulatory genes (24).…”
mentioning
confidence: 99%